Lever of Empire : The International Gold Standard and the Crisis of Liberalism in Prewar Japan - Metzler, Mark, 1957- (Book collections on Project MUSE., 2006)
This book, the first full account of Japan's financial history and the Japanese gold standard in the pivotal years before World War II, provides a new perspective on the global political dynamics of the era by placing Japan, rather than Europe, at the center of the story.